Antecedents of public confidence in police in a conflict zone: A multi‐stakeholder view. Issue 4 (8th February 2021) - Sharma, Dheeraj; Pandey, Shivendra Kumar; Kumar, Patanjal; Mishra, Madhurima
Abstract : Public confidence in Police produces valuable outcomes for society. The present paper explores the drivers of public confidence in Police in Kashmir, India. The data were collected from 277 citizens and 318 police personnel in Kashmir. The study examined the role of the image of Police, media, the neutrality of Police, and community policing in influencing public confidence in the Police. Results indicated that police personnel considered the neutrality of Police and the role of media as the most crucial determinants of public confidence. However, citizens' expectations were different. Citizens believed that community policing and the image of the Police were essential to elicit their confidence in the Police. The study is a novel attempt to empirically examine the gap between citizens' expectations and the Police's perception of those expectations in a conflict zone. The findings of this study would enable policymakers to design suitable interventions to secure public confidence in Police in a conflict zone.